Mapping the Intangibilities of the Historic Centre of Porto: ParticipA(C)TION (and its Challenges) in Cultural Mapping Projects - Romeiro, Patrícia (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2015)
This article focuses on cultural mapping projects as a strategy for urban development. In particular, it analyzes how one of the most important cultural mapping matrices – its participatory mission – can be operationalized. Moving away from other projects where participation is merely rhetoric or is interpreted with little depth (for example, exchange of information, consultation), the public project Manobras no Porto serves to analyze: 1) how a broad and deep concept of participation can be implemented in practice (and under what circumstances can it be successful) and 2) what kind of results can be achieved. In addition to the potential practical interest, the article also aims to contribute to deepening the debate on cultural mapping. The analysis clearly shows that participation involves a large and complex set of motivations and abilities, and that understanding how cultural mapping projects are developed (and their impact on the territory) requires that they be understood as exercises of negotiation between the agents involved.